Analisis Kepedulian Siswa SD Terhadap Kebersihan Lingkungan Sekolah di SDN Tanjung Jati 2 - Nurohma Dayani, Karina; Zulfatul Tsaniyah, Itsna; Badruddin; Firmansyah, Rachman; Tri Widyawati Zain, Yuniar; Sudi Pratikno, Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze elementary school students’ awareness of environmental cleanliness at Elementary School of Tanjung Jati 2. The problem underlying this research is the existence of students’ behaviors that indicate low concern for cleanliness, such as littering, low participation in cleaning activities, and the sub optimal implementation of character education habituation in schools. This study employs a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The results showed that the level of students' awareness of school environmental cleanliness was still relatively low and was influenced by several factors, including the role of teachers, school programs, habituation activities, and students' individual awareness. Forms of caring behavior demonstrated by students include maintaining classroom cleanliness, participating in cleaning activities such as “Clean Friday,” and disposing of waste properly. However, some students are still inconsistent in maintaining school cleanliness. Therefore, strengthening character education and implementing sustainable cleanliness programs are necessary to enhance students’ awareness and responsibility toward school environmental cleanliness.